Private equity investment committee paper on Pestana Hotel Group ? Market overview, investment thesis and operating model - Dias, Miguel Avelar Morgado Mourinho (2020)
This Work Project, take nin the context of a Private Equity Challenge, was developed by a group of four Nova Master’s in Finance students to meet only academic purposes and consists on a simulation of an Investment Committee Paper on Pestana Hotel Group. As the Portuguese based Group was the target of the developed project, the work coverssal the qualitative and quantitative aspects sof the company. A possible strategy, focusing on the operational side of the Hospitality segment, appears a san attractive Private Equity investment. This specific part focuses on the chapters of the capital structure and due diligence.